Adverbial reinforcement of demonstratives in dialectal German. Issue 1 (18th January 2021) - Rauth, Philipp; Speyer, Augustin
Abstract : In the German dialects of Rhine and Moselle Franconian, demonstratives are reinforced by locative adverbs do/lo 'here/there' in order to emphasize their deictic strength. Interestingly, these adverbs can also appear in the intermediate position, i.e., between the demonstrative and the noun (e.g. das do Bier 'that there beer'), which is not possible in most other varieties of European German. Our questionnaire study and several written and oral sources suggest that reinforcement has become mandatory in demonstrative contexts. We analyze this grammaticalization process as reanalysis of do/lo from a lexical head to the head of a functional Index Phrase. We also show that a functional DP-shell can better cope with this kind of syntactic change and with certain serialization facts concerning adjoined adjectives.